The BAHD Gene Family in Cacao (Theobroma cacao, Malvaceae): Genome-Wide Identification and Expression Analysis - Abdullah,; Faraji, Sahar; Heidari, Parviz; Poczai, Péter (Frontiers in Ecology and Evolution, 2021)
The benzyl alcohol O-acetyl transferase, anthocyanin O-hydroxycinnamoyl transferase, N-hydroxycinnamoyl anthranilate benzoyl transferase, and deacetylvindoline 4-O-acetyltransferase (BAHD) enzymes play a critical role in regulating plant metabolites and affecting cell stability. In the present study, members of the BAHD gene family were recognized in the genome of Theobroma cacao and characterized using various bioinformatics tools. We found 27 non-redundant putative tcBAHD genes in cacao for the first time. Our findings indicate that tcBAHD genes are diverse based on sequence structure, physiochemical properties, and function. When analyzed with BAHDs of Gossypium raimondii and Corchorus capsularis clustered into four main groups. According to phylogenetic analysis, BAHD genes probably evolved drastically after their divergence. The divergence time of duplication events with purifying selection pressure was predicted to range from 1.82 to 15.50 MYA. Pocket analysis revealed that serine amino acid is more common in the binding site than other residuals, reflecting its key role in regulating the activity of tcBAHDs. Furthermore, cis-acting elements related to the responsiveness of stress and hormone, particularly ABA and MeJA, were frequently observed in the promoter region of tcBAHD genes. RNA-seq analysis further illustrated that tcBAHD13 and tcBAHD26 are involved in response to Phytophthora megakarya fungi. In conclusion, it is likely that evolutionary processes, such as duplication events, have caused high diversity in the structure and function of tcBAHD genes.